Calidad microbiológica y físico-química del agua para usos recreativos en las playas de Bocagrande y Marbella,en Cartagena de Indias, Colombia. - Yepes Mayorga, Adriana (Revista Científica, 2006)
Cartagena is the more important Colombian port on the Caribbean Sea because its historical trajectory and tourist activity. Due to the importance that has the quality of the recreational waters for the swimmers, user in general, in this study were evaluated microbiology, physical, and chemical parameters during the months of February to April of 2004, that correspond to the summer time of the area. It was obeserved that the physical and chemical parameters, normalizes by the Ordinance 1594 of 1984, have a stationary behavior during the period of sampling and they fulfill the standards of this norm. About the microbiology parameters, dear average of total coliforms overcame the values that establish the norm. The results obtained for the parameter E. coli and enterococci, it was proceeded to compare them with some studies carried out by Cheung (1989) and Bandanarayake (1995), respectively.